Analisis Kualitas Pelayanan Kesehatan dengan Metode HEALTHQUAL dan Importance Performance Analysis (IPA) - Thamrin, M Husni; Tosungku, La Ode Ahmad Safar; Gunawan, Suwardi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Puskesmas X provides 12 services, including general polyclinic. This study measures service quality using the HEALTHQUAL method with five dimensions: empathy, tangible, safety, efficiency, and improvement, and determines improvement priorities through the IPA diagram. The results show an importance level of 4.277, with empathy at 4.283, tangible at 4.218, safety at 4.464, efficiency at 4.214, and improvement at 4.218. The performance level is 4.192, with empathy at 4.193, tangible at 4.124, safety at 4.104, efficiency at 4.270, and improvement at 4.255. Safety has the highest importance score (4.464), while efficiency has the highest performance score (4.270). Based on the IPA diagram, priority attributes for improvement include facility comfort, environmental safety, patient protection from infections, and trust in staff. Recommendations include re-arranging the waiting area, improving air circulation, providing handsanitizers, implementing SOPs for PPE, and evaluating staff performance. These improvements are expected to enhance service quality and trust in Puskesmas X.